Meta-analysis of multidecadal biodiversity trends in Europe - Francesca Pilotto (Nature Portfolio, 2020)
The global biodiversity decline might conceal complex local and group-specific trends. Here the authors report a quantitative synthesis of longterm biodiversity trends across Europe, showing how, despite overall increase in biodiversity metric and stability in abundance, trends differ between regions, ecosystem types, and taxa.